Vascular Effects of Polyphenols from Agrimonia eupatoria L. and Role of Isoquercitrin in Its Vasorelaxant Potential in Human Arteries - Jéssica Malheiros; Daniela M. Simões; Pedro E. Antunes; Artur Figueirinha; Maria Dulce Cotrim; Diogo A. Fonseca (MDPI AG, 2022)
Agrimonia eupatoria L. has been traditionally used for the treatment of inflammatory diseases but also as a hypotensive. To our knowledge, only one study has previously suggested an improvement in vascular endothelial function in diabetic conditions, as the underlying mechanisms and responsible compounds are unknown. In this study, we aimed to assess the direct vascular effects of Agrimonia eupatoria L. in human arteries. The infusion elicited a mild increase in basal vascular tone and a significant potentiation of the adrenergic contraction of 49.18% at 0.02 mg/mL, suggesting the presence of compounds with mild vasoconstrictor activity. In contrast, the ethyl acetate fraction inhibited adrenergic contraction by 80.65% at 2 mg/mL and elicited no effect on basal vascular tone. A potent concentration-dependent vasorelaxation was observed for both the infusion and the ethyl acetate fraction (maximal relaxation above 76% and 47%, respectively). Inhibition of nitric oxide synthase and cyclooxygenase elicited significant decreases in the vasorelaxation to the infusion, as, for the ethyl acetate fraction, only the cyclooxygenase pathway appeared to be involved. Isoquercitrin elicited a vasoactivity consistent with the ethyl acetate fraction, suggesting this is a major component responsible for the vasorelaxant properties of A. eupatoria. Further research is warranted to fully evaluate its vasoprotective properties with therapeutic potential in several conditions, e.g., atherosclerosis.